Influence of increasing amounts of supplemental alfalfa hay on intake and utilization of dormant, winter-harvested, bluestem-range forage by beef steers - E.S. Vanzant; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1991)
Sixteen, ruminally cannulated, beef steers were used in an intake/digestion experiment to determine the effects of supplementing a dormant, winter-harvested, bluestem range, forage diet with increasing amounts of moderate quality alfalfa. Steers were allowed ad libitum access to dormant forage and were supplemented with alfalfa hay at: 1) .23, 2) .47, 3).70, and 4) .94 % of BW on a dry matter (DM) basis. As the amount of supplemental alfalfa increased, dormant forage intake decreased, but total DM intake increased. Dry matter digestibility was unaffected by treatment, and only minor changes were noted for ruminal fermentation characteristics. Changes in ruminal fill and liquid dilution rates indicated an increase in digesta passage with increasing amounts of supplemental alfalfa hay. Although these results indicate that maximal digestible nutrient intake is attained at the highest level of supplementation, levels of nutrient intake and fermentation patterns indicate that adequate performance may be attained at lower levels of supplementation.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Protein Supplement; Winter range; Intake; Digestibility; Alfalfa